Low level light therapy by LED of different wavelength induces angiogenesis and improves ischemic wound healing. Issue 10 (31st October 2014) - Dungel, Peter; Hartinger, Joachim; Chaudary, Sidrah; Slezak, Paul; Hofmann, Anna; Hausner, Thomas; Strassl, Martin; Wintner, Ernst; Redl, Heinz; Mittermayr, Rainer
<x xml:space="preserve">Abstract</x> Background and Objective Low‐level light therapy (LLLT) has been revealed as a potential means to improve wound healing. So far, most studies are being performed with irradiation in the red to near‐infrared spectra. Recently, we showed that blue light (470 nm) can significantly influence biological systems such as nitric oxide (NO) metabolism and is able to release NO from nitrosyl‐hemoglobin or mitochondrial protein complexes. Therefore, the aim of this study was to evaluate and compare the therapeutic value of blue or red light emitting diodes (LEDs) on wound healing in an ischemia disturbed rodent flap model. Study Design/Materials and Methods An abdominal flap was rendered ischemic by ligation of one epigastric bundle and subjected to LED illumination with a wavelength of 470 nm (blue, n = 8) or 629 nm (red, n = 8) each at 50 mW/cm2 and compared to a non‐treated control group (n = 8). Illumination was performed for 10 minutes on five consecutive days. Results LED therapy with both wavelengths significantly increased angiogenesis in the sub‐epidermal layer and intramuscularly (panniculus carnosus muscle) which was associated with significantly improved tissue perfusion 7 days after the ischemic insult. Accordingly, tissue necrosis was significantly reduced and shrinkage significantly less pronounced in the LED‐treated groups of both wavelengths. Conclusions LED treatment of ischemia challenged tissue improved early wound healing by enhancing angiogenesis irrespective of the wavelength thus delineating this noninvasive means as a potential, cost effective tool in complicated wounds. Lasers Surg. Med. 46:773–780, 2014. © 2014 Wiley Periodicals, Inc.